Phase Separation-Controlled Assembly of Hierarchically Porous Aramid Nanofiber Films for High-speed Lithium-Metal Batteries - Jung, Arum; Lee, Michael J.; Lee, Seung Woo; Cho, Jinhan; Son, Jeong Gon; Yeom, Bongjun (Wiley - V C H Verlag GmbbH & Co., 2022)
The growth of lithium (Li) dendrites reduces the lifespan of Li-metal batteries and causes safety issues. Herein, hierarchically porous aramid nanofiber separators capable of effectively suppressing the Li dendrite growth while maintaining highly stable cycle performances at high charge/discharge rates are reported. A two-step solvent exchange process combined with reprotonation-mediated self-assembly is utilized to control the bimodal porous structure of the separators. In particular, when ethanol and water are used sequentially, aramid nanofibers form hierarchical porous structures containing nanopores in macroporous polymer frameworks to yield a mechanically robust membrane with high porosity of 97% or more. The optimized samples exhibit high ionic conductivities of 1.87-4.04 mS cm(-1) and high Li-ion transference numbers of 0.77-0.84 because of the ultrahigh porosity and selective affinity to anions. Li-metal symmetric cells do not show any noticeable presence of dendrites after 100 cycles, and they operate stably for more than 1500 cycles even under extreme conditions with a high current density of >20 mA cm(-2). In addition, the LiFePO4/Li full cell retains 86.3% of its capacity after 1000 cycles at a charge rate of 30 C.